Lipid peroxidation, serum iron and some antioxidants activities in pregnant women infected with HIV and malaria. Issue 1 (1st January 2021) - Idowu, Olufunmilayo A.; Adekoya, Victoria O.; Babalola, Ayodele S.; Audu, D.; Ademolu, Kehinde O.
ABSTRACT: This study determined the effects of malaria parasite and HIV infection on malondialdehyde (MDA), serum iron (Fe) and some enzymes activities of pregnant women in Abeokuta, Ogun State. A total of 251 pregnant women were enrolled for the study. Blood samples were collected from each consented pregnant women during ante-natal clinic for malaria test, HIV screening, MDA, Fe, gluthathione-S-transferases (GST), superoxides-dismutase (SOD) and peroxidase (PERO). The prevalence of malaria parasite infection and HIV in the study was 28.3% and 16.4%, respectively, while co-infection occurred in 8% of the population. Malaria prevalence increased with decrease in CD4 count. Though, HIV and malaria as single infection increased MDA and reduced serum iron values in the pregnant women (p < 0.05), MDA values were significantly higher (p < 0.05) in pregnant women with HIV and malaria co-infection. Reduction in SOD value was recorded in those with malaria and HIV co-infection but increased in other groups (p < 0.05). Serum PERO titer value in pregnant women with HIV and malaria co-infection was significantly lower (p < 0.05) compared with pregnant women infected with either HIV or Malaria. These results showed varying degrees of HIV and malaria-related oxidative stress in pregnant women.